Metode Pendidikan Islam Menurut Al-Qur’an - Nurzaman, Cepi; Nursafitri, Tuti; Holik, Abdul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Proper use of methods will largely determine the outcome of the educational and teaching process. Thus, educators must be good at choosing and using methods to match the material and teaching materials. Not to forget, as educators need to pay attention to several principles in the use of methods, so that teaching methods will lead to teaching success. The purpose of this study is to examine more deeply and identify Islamic education methods in the Quran. The method and type of data collection in this study is by library research by collecting books, journals and previous research results that support the research theme. This research data analysis technique uses a descriptive analysis approach. The stage begins with reducing data from library sources, then organizing and presenting data, verifying then ending with concluding data to answer the problem formulation. The results of this study show that the use of appropriate educational methods will have an impact on effective and efficient learning. This means that the method has a function and position and benefits in learning as described in the discussion description. In using the method, a teacher must also pay attention to the principle so that the use of the method remains colored with enthusiasm and direction. In addition, what distinguishes Islamic education methods from others is that all educational and learning activities must be in accordance with what has been outlined in the Qur'an as a reference and in accordance with the hadith